Discourse Markers in Argumentative Essay by the English Education Study Program’s Students of Universitas Bengkulu: A Cross-sectional Study - Khamidah Nurman; Safnil Arsyad; Zahrida - (Universitas Bengkulu, 2019)
This research is aimed to find the most frequent type of discourse markers used in the argumentative essay and the differences in its use written by the first, third, and fifth semester students of English Education study program of Universitas Bengkulu. The documentation technique and checklist are used in this research. Thirty two argumentative essays written by English Education Study Program’s students were analyzed by using mix method quantitative and qualitative, along with descriptive approach. The results showed that the most frequent type of discourse markers used by English Education students is additive markers (58%). And the students have different amount of discourse markers in their writing where the third semester students used more discourse markers than the other two group of students (148). It is highly encouraged for English Education instructors to take teaching discourse markers specifically into account. It is also suggested for future researchers to further analyze the correct use of discourse markers in the argumentative essay written by English Education Study Program students of Universitas Bengkulu.